Effets du type d`entraînement sportif sur le niveau d`excitabilité des motoneurones - Ben Cheikh, M.; Najimi, M.; Bigard, X.; Bahi, L. (Science & Sports, 2019)
Aims: To examine the effects of aerobic or anaerobic training on spinal neuronal plasticity using the Hoffmann reflex (H) and the M motor wave. This study proposes to discuss the hypothesis that these reflex responses can be used to estimate motor neuron excitability and spinal synaptic transmission. Methods: Four groups of 14 athletes each (sprinters, middle-distance athletes, footballers and swimmers) have accepted at the beginning of the sporting season to measure the power and explosiveness of Bosco's carpet jump at the level of the soleus. by dumbbells and H and M reflexes by electromyography. After 10months of training, the same variables were measured in both groups of athletes. Results: The comparison of Anova averages showed that the intergroup differences were all statistically significant (P<0.05) for the maximum amplitude of the H reflex and that the means of this variable decreased significantly (P<0.05) in the sprinters and increased significantly (P<0.05) in middle-distance athletes. In addition, the bilateral correlations between physical and electromyographic parameters were all significant (P<0.01) except for Mmax. However, comparisons between girls and boys did not reveal any significant results. Conclusion: These results suggest the existence of synaptic adaptation at the spinal level to explain the direction of the H-reflex evolution induced by the type of physical activity practiced (aerobic or anaerobic).